2004
DOI: 10.1039/b404477k
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of diorganotin(iv) moieties and 2-pyrazinecarboxylic acid: syntheses, characterizations and crystal structures of monomeric, polymeric or trinuclear macrocyclic compounds

Abstract: A series of diorganotin(IV) compounds of the type [R(2)Sn(pca)Cl](3)(R = CH(3); (n)Bu; C(6)H(5); C(6)H(5)CH(2); Hpca = 2-pyrazinecarboxylic acid), R(2)Sn(pca)(2)(mH(2)O)xnH(2)O (m= 1: R = CH(3), n= 2, R =(n)Bu, n= 0; m= 0, n= 0: R =(n)Bu, C(6)H(5), C(6)H(5)CH(2)) and (Et(3)NH)(+)[R(2)Sn(pca)(2)Cl](-)xmH(2)O (m= 0: R = CH(3), (n)Bu, C(6)H(5)CH(2); m= 1: R = C(6)H(5)) have been obtained by reactions of 2-pyrazinecarboxylic acid with diorganotin(iv) dichloride in the presence of sodium ethoxide or triethylamine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…Wang reported a monomer with 2,2 -biquinoline-4,4 -dicarboxylate and triphenyltin chloride [9]. In our previous work, we have also reported several novel molecular structures on it, such as two 15-membered trinuclear macrocyclic complexes with 2-pyrazinecarboxylic acid [10], and a series of triorganotin pyridinedicarboxylates with 2,5-, 3,5-, and 2,6-pyridinedicarboxylic acid [11]. To continue our research, we selected another interesting ligand, 2,2 -bipyridine-4,4 -dicarboxylic acid, on the basis of the following considerations: (a) the 2,2 -bipyridine and carboxylate functional groups of H 2 dcbp all have coordinate abilities, either singly or in unison, so several potential multiple molecular models in organotin complexes may be possess; (b) it can act not only as a hydrogen bond acceptor but also as a hydrogen bond donor, so the preparation of hybrid networks combining the strength of coordination bonding with the flexibility of hydrogen bonding is also feasible; and (c) it possesses high symmetry that may be helpful for the crystal growth of the product formed.…”
Section: Introductionmentioning
confidence: 95%
“…Wang reported a monomer with 2,2 -biquinoline-4,4 -dicarboxylate and triphenyltin chloride [9]. In our previous work, we have also reported several novel molecular structures on it, such as two 15-membered trinuclear macrocyclic complexes with 2-pyrazinecarboxylic acid [10], and a series of triorganotin pyridinedicarboxylates with 2,5-, 3,5-, and 2,6-pyridinedicarboxylic acid [11]. To continue our research, we selected another interesting ligand, 2,2 -bipyridine-4,4 -dicarboxylic acid, on the basis of the following considerations: (a) the 2,2 -bipyridine and carboxylate functional groups of H 2 dcbp all have coordinate abilities, either singly or in unison, so several potential multiple molecular models in organotin complexes may be possess; (b) it can act not only as a hydrogen bond acceptor but also as a hydrogen bond donor, so the preparation of hybrid networks combining the strength of coordination bonding with the flexibility of hydrogen bonding is also feasible; and (c) it possesses high symmetry that may be helpful for the crystal growth of the product formed.…”
Section: Introductionmentioning
confidence: 95%
“…In 1988, Lockhart established that the di-n-butyltin(IV) 3-thiopropionate exists in either oligomeric or monomeric form in solution and crystallizes as a cyclic hexamer [2]. Interestingly, in spite of these early findings only few organotin(IV)-macrocycles have been created [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], whereas a rich structural chemistry of stannoxane and distannoxane units containing supramolecules has been emerged [19][20][21][22][23][24][25][26][27][28][29]. Our entry in the field of organotin supramolecular chemistry began in 4 [30] and dimeric [Me 2 Sn(PhN 2 O 2 ) 2 ] 2 [31].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that organotin carboxylates have versatile molecular structures both in solid and in solution, such as monomers, dimers, tetramers, oligomeric ladders, hexameric drums, etc [15]. It has also been demonstrated that other structural types are formed owing to the presence of additional heteroatom sites (S, N, or O) along with a carboxylate moiety [10][11][12]16]. In our previous work, we have reported several new molecular structures of triorganotin complexes by the reaction of meso-dimercaptosuccinic acid (H 4 dmsa) and sodium ethoxide with triorganotin(IV) chloride in 1:4:4 stoichiometry [17].…”
Section: Introductionmentioning
confidence: 99%
“…Organotin complexes have attracted more and more attention in recent years, partly owing to their determinately or potentially pharmaceutical value, which have been reported several times before [1][2][3][4][5][6][7][8][9], as well as the versatile molecular structure and supramolecular architecture exhibited by these complexes [10][11][12][13][14]. It is well known that organotin carboxylates have versatile molecular structures both in solid and in solution, such as monomers, dimers, tetramers, oligomeric ladders, hexameric drums, etc [15].…”
Section: Introductionmentioning
confidence: 99%